MENDORONG PERUBAHAN MINDSET DAN PERLINDUNGAN HAK CIPTA KARYA DIGITAL DALAM MENGAKSELERASI TRANSFORMASI DIGITAL UNTUK MENJADIKAN UMKM KOTA BANDUNG NAIK KELAS - Nurani, Nina; Hermina, Nurul; Oktari, Sari Dewi; Marinda, Vina Silviani; Budiawan, Andi (Jurnal Abdimas Bina Bangsa, 2024)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays an important role in the national economy, especially in creating jobs and increasing people's income. Based on this, the implementing team held training and counseling activities related to the theme "Encouraging Mindset Changes and Digital Copyright Protection in Accelerating Digital Transformation to Make Bandung City MSMEs Move Up a Class". Community Service Activities in the form of presentations on global market business were held on July 31, 2024. A total of 15 MSME partners of the Bandung City Chamber of Commerce and Industry who attended this activity have businesses in the culinary, fashion, service and trade sectors. Based on the evaluation results, the activity went well and the training material was in accordance with work needs. The follow-up to this activity is the need for a sustainability program with the assistance of lecturers from the Faculty of Economics and Business, Widyatama University and the Bandung City Chamber of Commerce and Industry to encourage mindset changes and protection of digital copyright in facing digital transformation